واقع أدوار أمناء مراكز مصادر التعلم في المرحلة الابتدائية بمحافظة الأحساء - عمر, عمر موسى الحسن (Gezira Journal of Educational Sciences and Humanities; Vol 16 No 2 (2019), 2019)
هدفت الدراسة إلى معرفة دور أمناء وأمينات مراكز مصادر التعلم داخل المؤسسة التعليمية خاصة فيما يتعلق بمهامهم الإدارية، والتعليمية، والفنية، الوقوف على المعيقات التي تعيق أداءهم تلك المهام. حيث استخدمت الدراسة المنهج الوصفي التحليلي، وتكون مجتمعها من جميع أمناء وأمينات مراكز مصادر التعلم بالمرحلة الابتدائية بمحافظة الأحساء البالغ عددهم (205) فرداً، وطبقت الدراسة في الفصل الثاني للعام الدراسي 1439/1440هـ، قام الباحث بتوزيع استبانة إلكترونية لجميع أفراد المجتمع، واستجابت عينة بلغ قوامها (105) فرداً، وأظهرت نتائج الدراسة أنّ أمناء وأمينات مراكز مصادر التعلم يقومون بالأداء بدرجة مرتفعة جداً لكل من المهام الإدارية، ممثلة في موافقة الأمناء والأمينات على اختيار المعلمين للحصص، والمهام التعليمية ممثلة في تعاونهم مع المعلمين في تحديد أنماط نشاط التعلم المناسبة، بينما أظهرت النتائج أنّ أداء المهام الفنية جاء بدرجة مرتفعة ممثلة في تصنيفهم لمحتوى المركز وفق الفئات العمرية للتلاميذ، وكذلك أظهرت النتائج وجود معيقات بدرجة متوسطة تعيق أداء أمناء وأمينات مراكز مصادر التعلم في مدارس محافظة الأحساء الابتدائية لمهامهم، إذ إنّ من أبرزها: المعيقات الفنية التي تمثلت في عزوف المعلمين عن استخدام المراكز. توصي الدراسة بعدة توصيات من أهمها: تشجيع أمناء مراكز مصادر التعلم وأميناتها للمعلمين على استكشاف أساليب تعليمية جديدة، والتطوير المهني لأمناء وأمينات المراكز للقيام بمهامهم المختلفة. The aim of the study is to know the role of the directors of the learning resources centers within the educational institution, especially with regard to their administrative, educational and technical tasks, and to identify obstacles that impede their performance for these tasks. The study used the descriptive analytical method, and its population consists of all 205 directors and directors of the learning resource centers in the primary stage in Al-Ahsa Governorate during the second semester of the academic year 1439-1440. The researcher distributed an electronic questionnaire to all members of the society. A sample of 105 individuals responded. LRC secretariats perform very well for each of the administrative tasks, represented by the directors 'and secretaries' approval of the selection of teachers for the quotas. The educational tasks are represented in their collaboration with the teachers in determining the appropriate patterns of learning activity, the results of the study showed that there were a number of obstacles that hindered the performance of the directors and directors of the learning resource centers in the primary schools of Al-Ahsa governorate. The main obstacles were the teachers' reluctance to use the centers. The study concluded with a number of recommendations, the most important of which is to encourage the secretaries of the learning resources centers and the secretaries of the teachers to explore new teaching methods and professional development for the secretaries and secretaries of the centers to carry out their various tasks. Keywords: Learning Resource Centers, Directors and Directors, Educational Foundation, Al Ahsa.